Potenciales efectos del cambio climático sobre la distribución del hongo (Moniliophthora roreri Cif & Par) en el cultivo de cacao (Theobroma cacao) en Ecuador - Vilchez Ponce, Cruz Ruby (2021)
Cocoa is one of the most important agricultural crops in Ecuador. However, production is affected by the pathogenic fungus (Moniliophthora roreri Cif & Par) and in the long term the losses could be greater as a consequence of variations in the climate. This work aims to: Evaluate the climatic niche of the cocoa crop (Theobroma cacao) and the pathogenic fungus (Moniliophthora roreri Cif & Par) to identify possible changes in the potential geographic distributions and in the areas of crop-pathogen coexistence against climate change scenarios. For the modeling of the climatic niche, records of the presence of Moniliophthora roreri Cif & Par and Theobroma cacao were used, obtained from world and national databases, scientific and gray literature. Select the bioclimatic variables of WorldClim 1.4, (4 variables of temperature and 3 of precipitation), and the algorithm of maximum entropy MaxEnt to obtain the models. Models were obtained for the current scenario, intermediate RCP 4.5 and extreme RCP 8.5 for the year 2050. The potential geographical distribution of the phytopathogen and cocoa occurs mainly in the Coastal and Amazon region for the current scenario. Cocoa would increase its potential geographic distribution in the two future scenarios compared to the present. The phytopathogen would slightly decrease its potential geographic distribution in future scenarios compared to the present. Regarding the fungus-cocoa coexistence areas, the most susceptible areas are the tropical regions of the country such as the Coast and Amazonia for the present and future scenarios, representing a risk to cocoa cultivation, due to the invasion of the phytopathogen. For this reason, early warning measures will be adopted for the detection and control of the disease, focused on these risk areas for the conservation of biodiversity and food security in the country. Keywords: climate niche modeling, MaxEnt, potential geographic distribution.